Indikator Tawadhu dalam Keseharian - Purnama Rozak (Madaniyah, 2017)
Character in Islam known with the term akhlaq, namely the condition of being born and human inner. Akhlaq divided into akhlaq good and bad akhlaq. Akhlaq good or akhlaq mahmudah, as patient, thanksgiving, sincere, received, humble or tawadhu, honest or sidiq, philanthropist or jud, mandate, excusing, and gracefully. Akhlaq bad as petulant, do not give thanks, showy, voracious, arrogant, stingy, perfidious, revenge, and blasphemy. Indicators group this character quantitatively can be developed by involving the various the theory community close to support restrictions character good and bad above. Individual character behold a reflection of what is in individual self. Individuals can be expressing what is his power. The process of actual potential itself up to individual have to of domestic which need to actualized and which need to controlled. This factor more played by psychologists or counselor to map potential individuals and stretches, so formed to individuals characterless.